Realisasi Identitas Politik Luar Negeri Indonesia sebagai ‘Peace Maker’ melalui Constructive Engagement dalam Konflik Rohingya - Ali Muhsin; Barka Alhudaebi Nawawi; Surya Mahesa (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
Since its independence declaration, Indonesia has demonstrated its commitment to international diplomacy, upholding the principle of an independent and active foreign policy. One of the tangible manifestations of Indonesia’s role in the international arena is its identity as a ‘peace maker,’ which is reflected in the diplomatic efforts made to address the Rohingya conflict. This article explores Indonesia’s role in resolving the Rohingya conflict through a constructive engagement approach, particularly in multilateral diplomacy with the Organization of Islamic Cooperation (OIC) and bilateral diplomacy with Myanmar. In this diplomatic framework, Indonesia focuses on humanitarian and human rights approaches, encouraging the OIC to employ soft diplomacy to achieve peaceful solutions without resorting to violence. On the other hand, Indonesia also navigates challenges in bilateral diplomacy with Myanmar, which is reluctant to accept foreign intervention, by offering solutions based on dialogue and constructive cooperation. As a result, Indonesia has successfully established its identity as a peace-making nation on the global stage, reflecting not only an active foreign policy but also as a symbol of the country’s prestige, respected for its involvement in resolving international conflicts. This article aims to deepen the understanding of Indonesia’s contributions to global peace diplomacy and the relevance of the norms and values inherent in Indonesia’s foreign policy.